2001
DOI: 10.1046/j.1464-5491.2001.00413.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased secretion of TGF‐β1 by peripheral blood mononuclear cells from patients with Type 1 diabetes mellitus with diabetic nephropathy

Abstract: Type 1 diabetic patients with overt nephropathy show increased TGF-beta1 secretion by PBMC. Diastolic blood pressure levels correlated with TGF-beta1 secretion in diabetic patients with nephropathy. Increased TGF-beta1 secretion by PBMC may be associated with renal and vascular disease in Type 1 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…WBCs in diabetic patients may be activated by advanced glycation end products or reactive oxygen species (12-14) and cytokines (16). Activated leukocytes secrete many kinds of cytokines and transcription factors that have a crucial role in inflammat i o n , i n c l u d i n g T N F -␣ , NF-B , interleukin-1␤, and transforming growth factor ␤, thereby contributing to glomerulosclerosis (17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WBCs in diabetic patients may be activated by advanced glycation end products or reactive oxygen species (12-14) and cytokines (16). Activated leukocytes secrete many kinds of cytokines and transcription factors that have a crucial role in inflammat i o n , i n c l u d i n g T N F -␣ , NF-B , interleukin-1␤, and transforming growth factor ␤, thereby contributing to glomerulosclerosis (17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Polymorpho-and mononuclear leukocytes can be activated by advanced glycation end products (12), oxidative stress (13, 14), angiotensin II (15), and cytokines (16) in a state of hyperglycemia. Leukocytes may be activated through the release of cytokines, such as tumor necrosis factor-␣ (TNF-␣) (17,18), transforming growth factor ␤1 (19), superoxide (20), nuclear factor B (NF-B) (21), monocyte chemoattractant protein 1, interleukin-1␤, and others (17) to participate in the pathogenesis of diabetic micro-and macrovascular complications. Elevated differential cell counts, including counts of eosinophils, neutrophils, and monocytes, also predict the future incidence of CAD (11,22,23).…”
Section: Diabetes Care 28:1710 -1717 2005mentioning
confidence: 99%
“…Moreover, activated macrophages secrete factors such as PDGF that promote fibroblast proliferation (129). Increased secretion of TGF-␤ by peripheral blood mononuclear cells was reported in patients with type 1 DN (130). With respect to the interaction between macrophages and mesangial cells, it has been shown that the culture supernatant of macrophages can stimulate mesangial cells to produce fibronectin in vitro (131).…”
Section: Role Of Immune Cells In Endothelial Dysfunctionmentioning
confidence: 99%
“…Levels of plasminogen activator inhibitor-1 (PAI-1) and connective tissue growth factor (CTGF), both key mediators of profibrotic TGF-β activity, are also significantly increased in tissue and plasma of experimental and human diabetic nephropathy [15][16][17][18][19][20]. Furthermore, Korpinen et al have demonstrated increased secretion of TGF-β by 2-day cultured peripheral blood mononuclear cells (PBMCs) from patients with type 1 diabetes and showed an association of these TGF-β levels with the occurrence of diabetic nephropathy [21]. In contrast, renal expression of another member of the TGF-β superfamily, the antifibrotic bone morphogenetic protein 7 (BMP7), is decreased during the course of experimental diabetic nephropathy [22], and in vitro studies with human mesangial cells have revealed that a high glucose concentration induces the expression of BMP antagonists CTGF and gremlin [23,24].…”
mentioning
confidence: 99%